Structural and antibacterial properties of a γ‐radiation‐assisted, in situ prepared silver–polycarbonate matrix. Issue 36 (2nd June 2016) - Deore, A. V.; Hareesh, K.; Ramya, P.; Ianni, E.; Guagliardo, P.; Samarin, S.; Williams, J. F.; Sanjeev, G.; Dahiwale, S. S.; Kanjilal, D.; Dhole, N. A.; Kodam, K. M.; et al.
ABSTRACT: A silver–polycarbonate (Ag–PC) matrix was prepared by a γ‐radiation‐assisted diffusion method, and its antibacterial properties were studied. Rutherford backscattering spectroscopy, X‐ray diffraction, and transmission electron microscopy results showed the diffusion of good, crystalline‐structured (face‐centered cubic) silver nanoparticles (AgNPs) inside polycarbonate (PC) after irradiation. Ultraviolet–visible spectroscopic results indicated a blueshift in the surface plasmon resonance of the AgNPs; this revealed a particle size decrease with increasing γ‐radiation dose. This was also supported by the scanning electron microscopy results. The microstructure of the pristine PC and silver‐doped PC was monitored with positron annihilation spectroscopy, and it showed decreases in the free‐volume hole size and fractional free‐volume for Ag–PC and γ‐ray‐irradiated PC. This corroborated the Doppler broadening spectroscopy results. The thermal degradation temperature of PC was increased because of the diffusion of AgNPs in PC. The antibacterial activity of the synthesized Ag–PC matrix was evaluated by the zone of inhibition, and the results demonstrated its bacterial growth inhibition ability. The results indicate the potential to produce an Ag–PC matrix for various applications in medical and food industries. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43729. Abstract :